PMST: A custom Python-based Monte Carlo Simulation Tool for research and system development in portable pinhole gamma cameras - Jiang, Yangfan; Bugby, Sarah L.; Lees, John E. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2024)
A custom Python-based Monte Carlo Simulation Tool (PMST) has been developed to assist in the development of portable gamma cameras or the generation of simulated gamma image datasets, e.g. for deep learning. The simulation tool has been validated by comparison between theoretical and experimental results. PMST includes common attenuation interactions such as the photoelectric effect and Compton and Rayleigh scattering and fluorescence and non-radiative secondary effects. It allows users to simulate and visualise a gamma imaging system with multiple absorbers, flexible geometry, and different materials.